Health‐related quality of life and lifestyle changes in patients with chronic kidney disease and hyperkalaemia: Real‐world data from the US, five European countries and China. Issue 8 (17th May 2021) - Grandy, Susan; Jackson, James; Moon, Rebecca; Bluff, Daniel; Palaka, Eirini
Abstract: Background: Chronic kidney disease patients have impaired health‐related quality of life and an increased risk of hyperkalaemia. Aims: The objective was to evaluate the impact of hyperkalaemia on health‐related quality of life, and investigate lifestyle change recommendations, in these patients. Methods: The Adelphi Real World Chronic Kidney Disease Specific Programme™ was used. Data were collected from physicians and patients with non‐dialysis dependent stage 3a, 3b and 4 chronic kidney disease from the US, France, Germany, Spain, Italy, the UK and China. Patients completed the Kidney Disease Quality of Life Instrument and EuroQol‐5D‐3L. Analyses compared data between hyperkalaemic (serum potassium >5.0 mmol/L) and normokalaemic (serum potassium 3.5‐5.0 mmol/L) patients. Results: Overall, 1149 patients were included (hyperkalaemic: n = 216, normokalaemic: n = 933; US: n = 376, Europe: n = 490, China: n = 283). Hyperkalaemic vs normokalaemic patients experienced more symptoms ( P  < .001) and had numerically lower scores, indicating poorer health‐related quality of life, in all Kidney Disease Quality of Life domains, with significant differences for three/five domains. Hyperkalaemic patients reported numerically lower EuroQol‐5D‐3L utility index and visual analogue scores, indicating poorer health status, than normokalaemic patients. A higher proportion of hyperkalaemic than normokalaemic patients were recommended to reduce dietary potassium ( P  < .05). More normokalaemic than hyperkalaemic patients reported making a radical change in five/six recommended lifestyle changes, with the difference significant for four/six recommendations. Conclusions: Hyperkalaemia is associated with an incremental impairment of the health‐related quality of life in chronic kidney disease patients. A better understanding of the impact of hyperkalaemia in these patients could improve patient outcomes.